Penerapan Pembelajaran High Order Thinking Skill (HOTS) Pada Mata Pelajaran IPA Siswa Kelas V SDN 23 Kendari - Maria Selviana Fai; Kasmawati Kasmawati; Ridwan Ardi (FKIP UNSULTRA, 2025)
This study aims to describe the implementation of High Order Thinking Skill (HOTS) learning in science subjects at SD Negeri 23 Kendari. The results of the study indicate that teachers have implemented HOTS principles in planning and implementing learning, in accordance with the 2013 Curriculum. The Learning Implementation Plan (RPP) used includes operational verbs at cognitive levels C4 to C6, which encourage students to think critically, analytically, and creatively. Students are able to demonstrate these abilities through activities such as making mind maps and responding to learning evaluations. However, the implementation of HOTS learning online during the pandemic experienced obstacles that affected the effectiveness of the learning process. Supporting factors for HOTS implementation include the availability of learning media, a conducive school environment, and teachers who have a positive understanding and perception of HOTS. Conversely, inhibiting factors include variations in student abilities, limited facilities such as projectors and the internet, and obstacles to student attendance in online learning. Science learning with the HOTS approach has been proven to improve students' abilities in analyzing, evaluating, and creating solutions to real problems, making learning more meaningful and relevant in everyday life